(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background. Definitive evidence that exercise interventions that improve gait also reduce disability is lacking. A task-oriented, motor sequence learning exercise intervention has been shown to reduce the energy cost of walking and improve gait speed, but whether the intervention also improves activity and participation has not been demonstrated in chronic stroke. Objective: To investigate whether the task-oriented, motor sequence learning exercises act betterthan impairment-oriented multi-component exercises on gait parameters and efficiency in chronic stroke patients. Methodology: This study was a single-blind, experimental study.Setting. The study was conducted at‘Jain Neuro& IVF Hospital.The study participants were 45 older adults (mean age 55.93 years, SD4.85) with variable gait in chronic stroke. The intervention was a 3-week, physical therapist–guided program of Task oriented or Impact oriented. Measurements. confidence in walking determined with the Gait Efficacy.10-meter walk test evaluates gait velocity in chronic stroke patients using the Emory Functional Ambulation Profile (E-FAP).The items represent a range of challenges from level walking to walking on uneven surfaces, curbs, or stairs. .Conclusions. Task-oriented motor sequence learning exercises are effective in improving stride length, step length, cadence, and gait efficiency scale in chronic stroke patients. The task-oriented motor sequence learning exercises offered advantages over the impairment-oriented multicomponent exercises in terms of rate of learning and the ability to maintain the skill level achieved during training.